MOTIVASI MELALUI LAYANAN PESAN SINGKAT TELEPON SELULER PADA PERILAKU MEROKOK: Studi di Universitas Muhammadiyah Pontianak - Abduh Ridha (Berita Kedokteran Masyarakat (BKM), 2012)
MOTIVATION THROUGH CELLULAR PHONE SHORT MESSAGES IN SMOKING BEHAVIOR: A STUDY AT MUHAMMADIYAH UNIVERSITY OF PONTIANAK   Abduh Ridha1, Ira Paramastri2, Trisno Agung Wibowo3   ABSTRACT   Background: An emerging health problem in Indonesia nowadays is younger age of smokers both nationally and in some certain areas. They are student, but most of them have been addicted to cigarette smokers. Considering the characteristics of teenagers, counseling method based on transtheoritical commonly used recently is short messaging technology. Objective: To identify effect of smoking cessation motivation message through short messages to self-efficacy; decisional balance; intention to quit smoking; and quantity of cigarettes smoked. Method: The study was an experiment with pretest-posttest control group design. Population of the study were smoking students at Muhammadiyah University of Pontianak that were in the pre-contemplation phase. The study involved two groups, experiment and control each consisting of 100 students. Results: Students that got short message intervention of smoking cessation encouragement did not get significant score of efficacy (α>0.05). Score of decisional balance changed significantly in the experiment group. The score decreased as much as 0.85 after intervention of encouragement through delivered short message. The score decreased due to the decrease of score in pro as much as 0.58 and the increase of score in contra as much as 0.23 (α<0.05). Changes of score in decisional balance also influenced increase of intention (R2=63.9%; X2=0.00). After the intervention there was increasing of intention in the experiment group as much as 37.5% (α<0.05). Conclusion: Students that got encouragement through cellular phone short message had better balance of decision and intention than those that did not get encouragement.   Keywords: students, behavior, smoking, transtheoritical, smoking cessation   1 Muhammadiyah University of Pontianak 2 Faculty of Psychology, Gadjah Mada University 3 Health Departement of Yogyakarta Province